A Comparative Study of Encryption-Based Access Control Schemes in Ethereum, Hyperledger Fabric, and Corda - Mandinyenya, Godwin; Malele, Vusumuzi (Jurnal Ilmiah Computer Science, 2025)
Blockchain technology has emerged as a transformative solution for decentralized and immutable data storage, offering transparency and security across various industries. However, ensuring authorized data access remains a critical challenge in blockchain systems. Encryption-based access control mechanisms are pivotal in mitigating unauthorized access, yet their implementation varies significantly across different blockchain platforms. This study provides a comprehensive comparison of encryption-based access control schemes in three prominent blockchain platforms: Ethereum, Hyperledger Fabric, and Corda. The analysis focuses on their strengths, weaknesses, and suitability for various use cases, evaluating security, scalability, and usability. The findings reveal distinct trade-offs among the platforms, highlighting the need for tailored solutions based on specific application requirements. Future research directions, including hybrid access control models and post-quantum cryptography, are also discussed.